H3K4me2 accompanies chromatin immaturity in human spermatozoa: an epigenetic marker for sperm quality assessment - Štiavnická, Miriama; García-Álvarez, Olga; Ulčová-Gallová, Zděnka; Sutovsky, Peter; Abril-Parreño, Laura; Dolejšová, Martina; Řimnáčová, Hedvika; Moravec, Jiří; Hošek, Petr; Lošan, Petr; Gold, Lukáš; Fenclová, Tereza; et al. (Systems biology in reproductive medicine, 2020)
Chromatin remodeling, including histone post-translational modifications, during spermatogenesis can affect sperm quality and fertility, and epigenetic marks may therefore be useful for clinical evaluations of sperm. Together with histone hyperacetylation, the dimethylation of histone H3 on lysine K4 (H3K4me2) is also required during protamination. Accordingly, we evaluated the utilization of this epigenetic mark for the identification of sperm with decrease quality and immature chromatin. In this study, 99 semen samples, including 22 normozoospermic (N), 63 asthenozoospermic (A), and 14 oligoasthenozoospermic (OA) samples, were comprehensively analyzed with respect to H3K4me2 levels, DNA damage (DNA fragmentation index, DFI), and sperm immaturity (high DNA stainability, %HDS), as determined by a sperm chromatin structure assay using flow cytometry. We detected a significant relationship between H3K4me2 and %HDS (r = 0.47; p < 0.001). Furthermore, we observed negative correlations between H3K4me2 and sperm concentration, motility, and mitochondrial activity (p < 0.05). The increase in immaturity as semen quality decreased (N > A > OA) indicates the importance of chromatin immaturity and histone code deviations in sperm evaluations. Using various approaches, our study elucidated H3K4me2 as a molecular marker of sperm quality with potential use in reproductive medicine.Abbreviations: A: asthenozoospermic; AO: acridine orange; ART: assisted reproductive therapy; BWW: Biggers-Whitten Whittingham; DAPI: 4',6' -diamidino-2-phenylindole; DFI: DNA fragmentation index; H3K4me2: dimethylation of lysine K4 on histones H3; HDS: high DNA stainability; HRP: horseradish peroxidase; MACS: magnetic-activated cell sorting; N: normospermic; NGS: normal goat serum; OA: oligoasthenozoospermic; PTM: post-translational modification; SCSA: sperm chromatin structure assay; SUTI: sperm ubiquitin tag assay; TBS-T: TBS with 0.5% Tween-20.
Keywords: histony; Male; Semen Analysis; biologické markery; Biomarkers; Sperm DNA; epigenetics; restrukturace chromatinu; oligospermie; Methylation; metylace; chromatin immaturity; Adult; Spermatozoa; dospělí; Histone Code; mužské pohlaví; histonový kód; H3K4me2; lidé; Humans; Oligospermia; high DNA stainability; spermie; astenozoospermie; Histones; Asthenozoospermia; Chromatin Assembly and Disassembly; analýza spermatu